TINJAUAN YURIDIS TERHADAP PIDANA UANG PENGGANTI UNTUK PENGEMBALIAN KERUGIAN NEGARA DALAM PUTUSAN PERKARA NOMOR:01/PID.SUS-TPK/2018/PN.PDG - Husna, Rahmatul; Artina, Dessy; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In the Criminal Act Article 18 paragraph (1) of Law Number 3 of 1999 concerning Eradication of Criminal Acts. In general, there are still many who question the issue of collecting money, one of which is the criminal prosecution of corruption together. The judge dropped the loan of money to the defendant. The purpose of this thesis discussion, namely: First, understand money arrangements for corruption. Second, to find out the juridical decision on spending money on state spending for case decisions Number: 01 / Pid.Sus-TPK / 2018 / PN.Pdg.This type of research is normative legal research. This study is more specific to the principle research on the court's decision by reviewing, analyzing and analyzing various related literature which also discusses interviews with Kasubsi Extraordinary Efforts and Execution of the Special Crimes of the Padang District Attorney.From the results of the research conducted, it can be concluded, First, the criminal arrangement of substitute money is regulated in Article 18 paragraph (1) letter b of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning Eradication of Corruption. The compensation payment mechanism is regulated in the Supreme Court Regulation No. 5 of 2014 concerning Supplementary Criminal Money in Corruption Crime. While the process of billing and convicted person pays for the replacement money, the mechanism for payment of the replacement money is based on the decision of the Attorney General Number: Kep-518 / JA / 11/2001 dated November 1, 2001. the mistake and the role of the defendant so that they have not been able to apply justice, expediency and great proportionality to the community or to the defendant, in accordance with the objectives of the conviction.Author's Suggestions, First, the Judge should consider the facts that have been revealed in court so as to provide justice by providing appropriate and proportionate sanctions to the accused to provide justice for the perpetrators and victims. Second, in imposing a criminal sentence on the defendant, the Judge should pay attention to the benefits of the criminal sanction.Keywords: Judicial Review-Criminal Replacement Money